The Role of Product Placement in Serial Storytelling. - Mortara, Ariela; Roberti, Geraldina (Funes. Journal of narratives and social sciences, 2024)
In the last decades, TV series have increasingly become an ideal platform for product placement initiatives due to their relatively quick production process and the variety of advertising opportunities they offer through sound, visual or integrated placements (Russell, 2019). Moreover, in recent years, streaming platforms have further promoted this form of communication by creating serialized content that resonates strongly with younger audiences, who tend to favour non-traditional media (Li, 2023). The continued increase of global revenues further underscores the success of product placement, with projections anticipating a surge to $29 billion in 2023 (Navarro, 2023). This reflects a notable increase of over 12% compared to the preceding year. In this context, the paper aims to analyse product placement in the series And Just Like That..., the sequel to Sex and the City. In particular, it will focus on two antithetical cases: the so-called “negative placement”, which occurs when the inclusion of a brand or product is linked to a narrative element detrimental to the image of the brand itself, and “positive placement”, a promotional strategy that instead enhances the appeal and visibility of the featured product within the narration.